An UWB LNA Design with PSO Using Support Vector Microstrip Line Model - Salih Demirel; Filiz Gunes; A. Kenan Keskin (Journal of Applied Mathematics)
A rigorous and novel design procedure is constituted for an ultra-wideband (UWB) low noise amplifier (LNA) by exploiting the 3D electromagnetic simulator based support vector regression machine (SVRM) microstrip line model. First of all, in order to design input and output matching circuits (IMC-OMC), source ZS and load ZL termination impedance of matching circuit, which are necessary to obtain required input VSWR (Vireq), noise (Freq), and gain (GTreq), are determined using performance characterisation of employed transistor, NE3512S02, between 3 and 8 GHz frequencies. After the determination of the termination impedance, to provide this impedance with IMC and OMC, dimensions of microstrip lines are obtained with simple, derivative-free, easily implemented algorithm Particle Swarm Optimization (PSO). In the optimization of matching circuits, highly accurate and fast SVRM model of microstrip line is used instead of analytical formulations. ADCH-80a is used to provide ultra-wideband RF choking in DC bias. During the design process, it is aimed that Vireq = 1.85, Freq = Fmin, and GTreq = GTmax all over operating frequency band. Measurements taken from the realized LNA demonstrate the success of this approximation over the band.